POLICY OF HEALTH CHECK-UP ON PROSPECTIVE HAJJ PILGRIMS - Roslan, Rosidi; Darojat, Rofiud; RF, Mochamad Gesta; Nugraha, Andhika; Aimanah, Ira Ummu (Journal Philosophy of Law, 2024)
The purpose of this study is to investigate and analyze the health examination policy for Prospective Hajj Pilgrims (PHP) and the issues encountered. The research method employed is juridical-normative, using a legislative approach, with secondary data consisting of legislation and reference sources. The collected data were analyzed using descriptive-analytical techniques. The findings indicate that the PHP health examination program by the district health office has implemented the Minister of Health Regulation regarding PHP Health Isthita'ah through a first and second stage examination mechanism for determining health isthita'ah status which includes anamnesis, physical examination, supporting examinations, diagnosis, determination of health isthita'ah, recommendations, and follow-up plans on examination results. However, there are policy gaps regulating disease criteria that meet the istitaah requirements and are fit to fly at the third stage of inspection. There is no continuity of the first and second stage inspection policy with airworthiness. Technical instructions that regulate the limits of the health development program for PHP need to be adjusted to improve the health status of those PHP and provide certainty regarding the departure of PHP in terms of health.